Urgensi dan inovasi pendidikan agama Islam di perguruan tinggi umum - Nafidz, Arya Hanan (Maliki Interdisciplinary Journal, 2024)
This article reviews how Islamic Religious education is in the public tertiary environment. Which in this discussion shows the value of urgency or how important Islamic Religious education is in public tertiary institutions. This article is very useful for students especially, which provides an understanding of the importance of this discussion. Because, nowadays there are so many people who forget to apply Islamic values ​​on campus, such as ethics towards God, teachers, between friends, and so on. There are even those who think that these religious values ​​are an obstacle to development in education, even though these values ​​create advanced or superior education, as well as create prosperity, which is caused by the inculcation of religious values ​​in students. This type of article is a research article. Which data sources used are primary and secondary data, and researchers in their research use secondary data, such as journals, and so on. Therefore, in his research he did not go directly to the object. The impact of this discussion is to instill in young people, especially students, the urgency of Islamic religious education at public universities. Which of these results in students who excel and have religious character in their lives, thus creating an interesting educational atmosphere, namely a combination of academic and religious values ​​that go hand in hand.